Diseño de un modelo lógico y su plan de migración para la reestructuración de la red de la SUGEF - Román-Acuña, Alejandro (Instituto Tecnológico de Costa Rica, 2001)
The information that handles the companies nowadays is very sensitive, so that any type of person can enter them, even in the same company. For that reason different levels from security for users of a same network and much more strict levels of security for external users exist authorized and non authorized. The local area network of a company must maintain strict levels of security, so that the different users within the same company do not have access to servers and information that is there and that it is not incumbent on to the work that they make. For that reason, when a logical segmentation of a network is designed is necessary to as much define profiles of user as of servers, to identify exactly as entrance they make the users to the servers and who type of information get in. In order to solve this problem the present equipment of network allows to make virtual designs of LAN (VLAN), that allows to create a network within a same equipment of network with no need to spend more resources, but increasing the security and efficient use of the network. But when making this design is due to know clearly as the network is structured, is due to analyze aspects of physical design of the building, technical characteristics of the equipment, routing protocols, structured wiring, among others, to really know if that change is necessary and as soon as it can hit that change to the network for his correct operation. Soon of the analysis of all these variables, it is necessary to make a plan of migration adapted to the time and dedication of the personnel in charge of the area of data, considering that stops the east user change must be transparent and to assure the monitoring and correct operation once made the change. Finally the existing technologies of VoIP and the characteristics of quality were investigated on watch that must fulfill this so that it can be implemented on the proposed logical design and the present equipment that the network has.
Proyecto de Graduación (Bachillerato en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2001.
Keywords: Segmentación; Lógica; Programación lógica; Información; Variables